Integration of measurable residual disease by WT1 gene expression and flow cytometry identifies pediatric patients with high risk of relapse in acute myeloid leukemia - Ahmed, Sonia; Elsherif, Mariam; Yassin, Dina; Elsharkawy, Nahla; Mohamed, Ayman S.; Yasser, Nouran; Elnashar, Amr; Hafez, Hanafy; Kolb, Edward A.; Elhaddad, Alaa (Frontiers in Oncology, 2024)
Background: Molecular testing plays a pivotal role in monitoring measurable residual disease (MRD) in acute myeloid leukemia (AML), aiding in the refinement of risk stratification and treatment guidance. Wilms tumor gene 1 (WT1) is frequently upregulated in pediatric AML and serves as a potential molecular marker for MRD. This study aimed to evaluate WT1 predictive value as an MRD marker and its impact on disease prognosis. Methods: Quantification of WT1 expression levels was analyzed using the standardized European Leukemia Network real-time quantitative polymerase chain reaction assay (qRT-PCR) among a cohort of 146 pediatric AML patients. Post-induction I and intensification I, MRD response by WT1 was assessed. Patients achieving a ≥2 log reduction in WT1MRD were categorized as good responders, while those failing to reach this threshold were classified as poor responders. Results: At diagnosis, WT1 overexpression was observed in 112 out of 146 (76.7%) patients. Significantly high levels were found in patients with M4-FAB subtype (p=0.018) and core binding fusion transcript (CBF) (RUNX1::RUNX1T1, p=0.018, CBFB::MYH11, p=0.016). Following induction treatment, good responders exhibited a reduced risk of relapse (2-year cumulative incidence of relapse [CIR] 7.9% vs 33.2%, p=0.008). Conversely, poor responders' post-intensification I showed significantly lower overall survival (OS) (51% vs 93.2%, p<0.001), event-free survival (EFS) (33.3% vs 82.6%, p<0.001), and higher CIR (66.6% vs 10.6%, p<0.001) at 24 months compared to good responders.Even after adjusting for potential confounders, it remained an independent adverse prognostic factor for OS (p=0.04) and EFS (p=0.008). High concordance rates between WT1-based MRD response and molecular MRD were observed in CBF patients. Furthermore, failure to achieve either a 3-log reduction by RT-PCR or a 2-log reduction by WT1 indicated a high risk of relapse. Combining MFC-based and WT1-based MRD results among the intermediate-risk group identified patients with unfavorable prognosis (positive predictive value [PPV] 100%, negative predictive value [NPV] 85%, and accuracy 87.5%). Conclusion: WT1MRD response post-intensification I serves as an independent prognostic factor for survival in pediatric AML. Integration of WT1 and MFC-based MRD results enhances the reliability of MRD-based prognostic stratification, particularly in patients lacking specific leukemic markers, thereby influencing treatment strategies.